Controlled alternate partial root-zone irrigation its physiological consequences and impact on water use efficiency - Kang, Shaozhong (Journal of experimental botany, 2004)
Controlled alternate partial root-zone irrigation (CAPRI), also called partial root-zone drying (PRD) in other literature, is a new irrigation technique and may improve the water use efficiency of crop production without significant yield reduction. It involves part of the root system being exposed to drying soil while the remaining part is irrigated normally. The wetted and dried sides of the root system are alternated with a frequency according to soil drying rate and crop water requirement. The irrigation system is developed on the basis of two theoretical backgrounds. (i) Fully irrigated plants usually have widely opened stomata. A small narrowing of the stomatal opening may reduce water loss substantially with little effect on photosynthesis. (ii) Part of the root system in drying soil can respond to the drying by sending a root-sourced signal to the shoots where stomata may be inhibited so that water loss is reduced. In the field, however, the prediction that reduced stomatal opening may reduce water consumption may not materialize because stomatal control only constitutes part of the total transpirational resistance. The boundary resistance from the leaf surface to the outside of the canopy may be so substantial that reduction in stomatal conductance is small and may be partially compensated by the increase in leaf temperature. It is likely that densely populated field crops, such as wheat and maize, may have a different stomatal control over transpiration from that of fruit trees which are more sparsely separated. It was discussed how long the stomata can keep 'partially' closed when a prolonged and repeated 'partial' soil drying is applied and what role the rewatering-stimulated new root growth may play in sensing the repeated soil drying. The physiological and morphological alternation of plants under partial root-zone irrigation may bring more benefits to crops than improved water use efficiency where carbon redistribution among organs is crucial to the determination of the quantity and quality of the products